Qualitative examination into the management accounting tools in use in petronas: evolutionary or traditionally steered? - Annuar, Hairul Azlan; Ahmed Haji, Abdifatah; Alam, Mahfuzul; Demikha, Lotfi (2012)
The main objective of this study is to investigate the current management accounting practices (MAPs) in the Malaysian context. More specifically, the paper aims to identify the traditional management accounting (MA) tools that are adopted in Malaysia and further investigates whether the traditional tools evolved into contemporary ones. The paper also examined why certain tools are used over others. The data in this study is obtained from one of the top 30 firms in Malaysia through interview means. The paper represents a report which forms part of a larger research into the evolution of management accounting tools in Malaysian public listed companies (PLCs), whereby a total of 10 PLCs of varying sizes and affiliations were chosen. The semi-structured interview was held with three executives in the Financial and Management Accounting Department of the concerned company. The company examined was chosen as it provided some illustrations of the adoption of both traditional MAPs and contemporary tools in its 2009 company annual report. Hence, the company was not chosen at random, but was selected after revealing the issues of the concern in its annual report (see, Eisenhardt, 1989; Chenhall and Smith, 1998b). The overall findings of the study indicated the use of both traditional and contemporary MA tools. Interestingly, the investigated company put equal emphasis on both the traditional and contemporary tools. New tools such as key performance indicators (KPI) and benchmarking that prior studies did not examine in the Malaysian context were among the contemporary tools identified in this study. However, consistent with prior studies (e.g., Chenhall and Smith, 1998a; Joshi; 2001), the main tool used in the examined company was found to be budgeting. The findings of the present study give an important implication for both companies in Malaysia as well as academicians. Firms may emulate the contemporary practices adopted by the investigated company. The findings also enlighten for future researchers new tools that need to be further explored in a large sample size. Despite that the study is one of few that qualitatively extend the area of MAPs in Malaysia, yet it is subjected to several limitations. One of the main limitations is due to a small sample size, thus, extra attention should be exercised in drawing conclusions to the wider population. Initial findings from the research conducted over the 10 companies suggest that large Malaysian PLCs and PLCs with foreign affiliations tend to adopt contemporary tools in addition to a either a modified or unmodified version of the traditional tools. Small and local affiliated PLCs appear to only depend upon traditional tools.